17th AIAA/CEAS Aeroacoustics Conference (32nd AIAA Aeroacoustics Conference) 2011
DOI: 10.2514/6.2011-2874
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Noise Reduction Of Linear Cascades With Trailing Edge Serrations

Abstract: The noise reduction potential of trailing edge serrations in a linear cascade of seven loaded airfoils is investigated experimentally for Re= 5.5 × 10 5 and M= 0.23. Turbulent boundary layer trailing edge noise is considerably reduced in the low-to mid-frequency range similarly to previous isolated airfoil investigations. A high frequency noise increase is also found for St= fδ/U > 1.2. The cascade effect is neither found to enhance nor to limit the noise reduction of serrations, except in the very low frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…The straight trailing edge shows higher u ′ RMS and v ′ RMS on the suction side which continues downstream while another region of higher RMS is seen to originate from the trailing edge. This behavior was previously observed in the PIV measurements conducted in Finez et al (2011). The serrated trailing edge with ϕ = 6 • shows this effect as well, and this region of increased fluctuations is seen to originate from the root of the serrations.…”
Section: Turbulence Statisticssupporting
confidence: 80%
See 3 more Smart Citations
“…The straight trailing edge shows higher u ′ RMS and v ′ RMS on the suction side which continues downstream while another region of higher RMS is seen to originate from the trailing edge. This behavior was previously observed in the PIV measurements conducted in Finez et al (2011). The serrated trailing edge with ϕ = 6 • shows this effect as well, and this region of increased fluctuations is seen to originate from the root of the serrations.…”
Section: Turbulence Statisticssupporting
confidence: 80%
“…While wind tunnel experiments have revealed that a reduction in noise is often measured when using serrations, a slight increase in noise at relatively higher frequencies has also been reported (Moreau et al 2011;Gruber 2012). It has been argued in Dassen et al (1996) and Oerlemans et al (2009) that the noise increase at higher frequencies might be due to the misalignment of the serrations with the flow in the wake of the airfoil. Gruber et al (2011) has ascribed this phenomenon to an increased turbulence activity between the serration teeth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the fan-OGV sources, Trailing Edge(TE) noise significantly contributes engine broadband noise 2 . TE noise source has first been characterized experimentally by Brooks & al.…”
Section: Introductionmentioning
confidence: 99%